Effect on microstructure and corrosion resistance of semi-solid slurry of 7A04 aluminum alloy by electromagnetic stirring. (6th January 2021) - Zhu, Yanli; Xu, Xiaolong; Zhao, Junwen; Hu, Guangzhong
Abstract: The microstructures and corrosion resistance of electromagnetic stirring (EMS) semi-solid slurry and as-cast 7A04 aluminum alloy were compared in this work. The results show that the primary microstructure of the as-cast 7A04 aluminum alloy is mainly dendritic and columnar dendrite with obvious elements segregation. In contrast, semi-solid processing can effectively form homogeneous and round primary α -Al grains, and significantly reducing element segregation. In addition, the main phases of the two forming methods (as-cast and semi-solid) both involved α -Al, η -MgZn2, θ -Al2 Cu. With the decrease of solidification temperature, the semi-solid alloy formed by electromagnetic stirring increases the precipitation of brittle phase S-Al2 CuMg. The self-corrosion potential of the semi-solid alloy is greater than that of the as-cast alloy, and the polarization curve has obvious passivation characteristics. Semi-solid processing could improve corrosion resistance of 7A04 aluminum alloy obviously.